A Cross-Sectional Study on the Readiness of Dentistry Specialty Students in the Role of Associate Educator - Hüseyin Hatırlı; Alem Coşgun; Işıl Sarıkaya (European Annals of Dental Sciences)
Aim: Our study aims to contribute to the literature by self-evaluating Dentists who graduated from different universities in our country, in the departments where they currently receive specialization training on Communication, Adaptation Skills, Information Management, Thinking and Problem Solving, and Professionalism.Methods: Research assistants who received specialist training in 8 departments of Tokat Gaziosmanpaşa University Faculty of Dentistry and who had not completed the first year of their education were included in the study. Participants were asked to participate in a ten-question survey on an entirely voluntary basis. When comparing the means of quantitative variables between groups, the Significance of the Difference Between Two Means test was used. Cross-tabulations and chi-square tests were used to evaluate whether there was a relationship between qualitative variables. p values were considered statistically significant when calculated to be less than 0.05.Results: According to the results obtained from our study, 78% of the speciality students reported that they thought that the clinical practice training they received during their student years was sufficient to educate clinical students, and 87.8% reported that they did not have communication problems with clinical practice students. While the answer to the question "The treatment planning I make in my clinical practice is compatible with the faculty member's planning" was 95.1% agree, 51.2% of the participants answered that they agreed with the question "I feel competent enough to solve any problem I encounter in clinical practice on my own." Conclusion: All participants are eager to learn different treatment methods related to the cases they encounter in clinical practice. Likewise, the vast majority reported that they were willing to develop new tools and techniques for use in clinical practice. This situation is promising for the future of our profession.Keywords: Dental Specialty Student; Dentistry Clinical Practice Training; Teamwork.